Implantação de um programa piloto de coleta seletiva em um Centro de Ciências da Saúde da UFES - Manzano, Maurício Faria Dame (2009)
The study present the steps of implementation and operation of a recycling collection of non-hazardous solid waste in a higher education center located on a university campus in the health area, to measure the amount of hazardous waste present into recyclable solid waste collected, and then to verify the influence of an environmental campaign to change the amount and quality default of the solid waste. The sample was collected in the inner part of the campus academic area and in the external area of the main health care establishments of campus, which evaluated all the collected recyclable material in the period of four months. The study also included a survey with 388 campus groups and eight weight campaigns of the non-hazardous solid waste and the healthcare solid waste. The daily average generation of solid waste on campus was 1,697.67 kilograms (in school time) and 8.02 kg selectively collected in the academic center (in school time after the beginning of the environmental campaign). Due to the deviation of the solid waste from the recyclable containers, one intervention was performed which indicated that the training of the cleaning teams should be improved. Although it has been verified an increase in the contribution of the recycled solid waste after the beginning of the environmental campaign in 99%, which was expected, there was verified an 890% increase in the potentially hazardous waste, indicating the need for a environmental campaigns implementation mainly directed to reduce inappropriate packaging of waste.